THE DYNAMIC BEHAVIOR OF SYSTEMS WITH ASYMMETRIC PIECEWISE AND LINEAR ELASTIC CHARACTERISTICS - Volkova, V. Ye. (Science and Transport Progress, 2003)
In a theoretical study of oscillations the necessity of building a mathematical model arises. For this purpose the data of technical drawings, descriptions, and also other documentation about the structure and meaning of separate parameters, will be used. However in some cases this information can be insufficient. An effective solution in this case can be usage of systems identification methods. They consist in construction of a mathematical model of the object, basing on experimental records.